A method for preparing a highly oriented structural thick film
By forming a dynamic shear flow field in the two-dimensional nanosheet gel film layer, the orientation of the two-dimensional nanosheet layer is induced, and the problem of difficulty in efficiently preparing highly oriented thick films in the prior art is solved, and efficient and continuous batches are achieved Prepared for a wide range of high-performance material applications.
Patent Information
- Application Number
- CN202310124633.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-02-16
AI Technical Summary
The prior art is difficult to efficiently induce the orientation arrangement of disordered two-dimensional sheets in large-thick continuous liquid films, and it is impossible to prepare a highly oriented thick film of two-dimensional sheet base structure on a large scale, which seriously restricts the orientation of two-dimensional nanosheet base structure. Large-scale application of thick films.
By inserting multiple straight lines into the interior of the two-dimensional nanosheet gel film layer, a dynamic shear flow field is formed, and the two-dimensional nanosheet layer is induced to undergo collective orientation in the direction of shear stress, and it changes from a random disordered state to a highly oriented structure.
A high-oriented thick film with a structural orientation factor of 0.91-0.99 is achieved within the thickness of 80μm-400μm. It is highly efficient and suitable for continuous batch preparation, and is suitable for thermal conductivity, mechanics and electromagnetic shielding.
Smart Images

Figure CN116253917B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano material and structure preparation, and more specifically to a method for preparing a highly oriented structure thick film. Background Art
[0002] Two-dimensional nanomaterials such as graphene and boron nitride nanosheets have completely different physical and chemical properties from three-dimensional materials, especially in terms of electrical conductivity, thermal conductivity, large specific surface area, and assembly ability. Therefore, they are important structural units for assembling and constructing three-dimensional macroscopic materials with specific excellent properties, and are also important fillers for forming composite systems with excellent properties when combined with other materials. Taking graphene, a typical representative of two-dimensional nanomaterials, as an example, the thermal conductivity of a single atomic layer of graphene sheets is measured to exceed 5000W / (mK), while the thermal conductivity of perfect graphite crystal highly oriented pyrolytic graphite (HOPG) is only about 2000W / (mK). When assembling and constructing macroscopic materials, the lateral thermal conductivity of a macroscopic graphene film assembled from graphene sheets can exceed 1500W / (mK) when the thickness is about 100μm, which is significantly better than the graphite film of the same thickness pressed from expanded graphite (~800W / (mK)). Therefore, graphene thermal conductive film has been commercialized in the field of thermal management of electronic devices, providing a new solution for the heat distribution of high power density devices and solving local hot spots, and has become the mainstream choice for 5G flagship phones of leading communication terminal companies. However, with the continuous improvement of the integration of electronic devices, the continuous increase in power density has become a development trend. Further improving the thermal conductivity of graphene thermal conductive film at high thickness is an inevitable requirement to support the application of graphene thermal conductive film in consumer electronics and other fields.
[0003] Whether as a structural unit or a composite filler, the performance of macroscopic materials and composite systems constructed by two-dimensional nanosheets is heavily dependent on the orientation of the sheets in the macroscopic structure and composite system. Random disordered orientation is conducive to the construction of isotropic structures and systems, while regular orientation along a specific direction is conducive to the construction of anisotropic structures and systems. Among them, regular orientation is very important for the expression of excellent properties such as thermal conductivity and electrical conductivity of two-dimensional sheets in the macroscopic structure. It is the key to building high-performance structures and composite systems, an important research direction in the field of two-dimensional materials, and a core technology for preparing macroscopic structures and systems such as high-performance thermal conductive films, shielding films and mechanical films. The orientation of thin (generally less than 30μm thick) layer structures is relatively simple, but many practical application scenarios require large size and thickness (generally greater than 50μm thick) while oriented structure. Coupled with the demand for efficient and continuous preparation, structural orientation technology faces important bottlenecks. The document Nature Communications (2018) 9:3484 reported a method of inducing the orientation of graphene sheets in a graphene hydrogel film layer by using the shear force and centrifugal force formed by a rotating barrel. The mechanical strength of the resulting graphene film reached 660MPa, which was about 3.3 times higher than that of the graphene film without orientation treatment. The document Composites: Part A 157 (2022) 106933 reported the use of a magnetic field to induce the orientation of boron nitride sheets in an epoxy resin matrix in a direction perpendicular to the composite film surface, so that the thermal conductivity in the vertical direction reached 14.55W / (mK), which was 4.5 times higher than that of an isotropic composite film of the same component that was not oriented by a magnetic field. The document Nature 448 (2007) 457 reported the use of a vacuum filtration method to prepare an oxide graphene film. Under the induction of a flow field, the graphene sheets were oriented and arranged, and the Young's modulus of a 5.5μm thick film layer could reach up to 42GPa. In addition, techniques such as ice template method (Advanced Materials 28 (2016) 6719), extrusion molding (Carbon 162 (2020) 455) and electric field induction (Journal of American Ceramic Society (2012) 95: 369; Ceramics International 42 (2016) 8657) have also been used to induce the orientation of two-dimensional nanosheets in the construction of macroscopic structures and systems. However, for the continuous preparation of oriented structures, the existing methods have obvious shortcomings in efficiency. The suction filtration method is a common method for preparing ordered structure films in the laboratory, but the two-dimensional sheets are very easy to clog the filter membrane due to their own structural characteristics, and cannot be prepared continuously, resulting in the suction filtration method being simple and easy but the efficiency of preparing thick films is extremely low. The rotary centrifugation method and ice template method have high efficiency in preparing thick films in a single batch, but cannot achieve continuous preparation. Due to the limitations of the rotating barrel diameter and the size of the freeze dryer, it is difficult to increase the size of a single batch.Extrusion molding and other methods can achieve continuous preparation by using flow field to induce sheet orientation, but the flow field is limited to the sheet on the surface of the flow channel, and the internal orientation of the structure cannot be controlled, and the overall orientation of the prepared thick film is poor. The orientation force of control technologies such as electric and magnetic fields is weak, and cannot match the high solid content and high viscosity system required for the preparation of thick structures, which is not conducive to the continuous and efficient preparation of oriented structures and systems.
[0004] In summary, due to inherent limitations, existing technologies make it difficult to efficiently induce the orientation of disordered two-dimensional sheets in thick continuous liquid films, and are unable to continuously prepare highly oriented thick films based on two-dimensional sheet structures on a large scale, which severely restricts the large-scale application of oriented thick films based on two-dimensional nanosheet structures. It is urgent to develop new structural orientation technologies that can simultaneously meet the requirements of high efficiency, high degree of orientation and continuous preparation. Summary of the invention
[0005] The present invention aims to provide a method for preparing a highly oriented structure thick film, which is suitable for efficiently inducing the spatial orientation of two-dimensional nanosheets in a liquid phase system to continuously batch prepare two-dimensional sheet-based thick films with a highly oriented structure.
[0006] According to the preparation method of the highly oriented structural thick film of the present invention, it comprises the following steps: S1, dispersing two-dimensional nanosheets in a solvent to obtain a two-dimensional nano dispersion with a mass concentration (solid content) between 0.5wt% and 7.0wt%; S2, spreading the two-dimensional nano dispersion on the surface of a substrate to form a first gel film layer with randomly oriented sheets; S3, inserting a plurality of straight lines into the interior of the first gel film layer to induce a shear flow field for orientation treatment to form a second gel film layer with highly oriented sheets, wherein the plane where the plurality of straight lines are located is parallel to the plane of the substrate and the spacing between adjacent straight lines is between 0.1mm and 0.5mm, and the straight lines and the first gel film layer move relative to each other in a direction parallel to the plane of the substrate, and the relative movement is a translation with a speed between 3mm / s and 16mm / s or a rotation with a rotation speed between 600rpm and 1100rpm; S4, drying the second gel film layer to obtain a two-dimensional nanosheet-based thick film with a high degree of structural orientation.
[0007] The present invention utilizes the movement of a straight line in a liquid phase to generate a uniform, continuous and controllable flow field in the entire liquid phase, and utilizes the shear flow field to induce the randomly distributed two-dimensional sheets in the liquid phase to collectively orient in the direction of the shear stress, thereby transforming from a random disordered state to a highly oriented structure. Due to the flexible wiring method, the present invention can introduce a shear flow field that penetrates the liquid phase system and runs through the liquid phase system in the entire liquid phase system by increasing the number of lines and reducing the line spacing, etc., and can completely cover the entire space without leaving a "blind spot" even when the size of the liquid phase system is large, and can be well compatible with traditional continuous film-forming processes such as scraping, thereby solving the contradiction between efficiency and orientation in traditional film-forming methods, and is very suitable for continuous batch preparation of two-dimensional nanosheet-based thick films with high orientation.
[0008] Preferably, the two-dimensional nanosheet is a graphene sheet, a graphene oxide sheet, a boron nitride nanosheet or a molybdenum disulfide nanosheet.
[0009] Preferably, the solvent is water and / or an organic solvent. In a preferred embodiment, the organic solvent is 1-methyl-2-pyrrolidone or isopropanol.
[0010] Preferably, the two-dimensional nano-dispersion liquid is a composite system comprising an inorganic material or an organic resin. In a preferred embodiment, the composite system comprises polyvinylidene fluoride with a mass concentration (solid content) of 5 wt%.
[0011] Preferably, the mass concentration (solid content) of the two-dimensional nanosheets in the two-dimensional nano-dispersion liquid is between 1wt% and 6wt%. More preferably, the mass concentration (solid content) of the two-dimensional nanosheets is between 1.5wt% and 3wt%.
[0012] Preferably, the viscosity of the two-dimensional nano-dispersion liquid is 7000cps-45000cps. More preferably, the viscosity of the dispersion liquid is 7273cps-43480cps. More preferably, the viscosity of the dispersion liquid is 11140cps-43280cps. More preferably, the viscosity of the dispersion liquid is 19850cps-31050cps. In a preferred embodiment, the viscosity of the dispersion liquid is 19930cps.
[0013] Preferably, the substrate is a film material, a tank body or a mesh plate. In a preferred embodiment, the substrate is PET.
[0014] Preferably, the thickness of the first gel film layer is 3 mm to 20 mm. More preferably, the thickness of the first gel film layer is 5 mm to 15 mm. In a preferred embodiment, the thickness of the first gel film layer is 7 mm.
[0015] Preferably, the material of the straight line is metal, polymer, carbon fiber or a composite material thereof. In a preferred embodiment, the straight line is aluminum wire, carbon fiber wire or polyester fiber wire.
[0016] Preferably, the diameter of the straight line is 0.1 mm-0.5 mm. In a preferred embodiment, the diameter of the straight line is 0.2 mm.
[0017] Preferably, the spacing between adjacent straight lines is 0.2 mm-0.3 mm.
[0018] Preferably, the translation speed is between 4 mm / s-15 mm / s, and the rotation speed is between 700 rpm-1000 rpm. More preferably, the translation speed is between 7 mm / s-10 mm / s, and the rotation speed is between 700 rpm-1000 rpm.
[0019] Preferably, the thickness of the two-dimensional nanosheet-based thick film is 80 μm-400 μm. More preferably, the thickness of the two-dimensional nanosheet-based thick film is 88.2 μm-387.7 μm. More preferably, the thickness of the two-dimensional nanosheet-based thick film is 162.4 μm-355.2 μm. More preferably, the thickness of the two-dimensional nanosheet-based thick film is 197.3 μm-296.1 μm. In a preferred embodiment, the thickness of the two-dimensional nanosheet-based thick film is 223.4 μm.
[0020] Preferably, the structural orientation factor of the two-dimensional nanosheet-based thick film is 0.91-0.99. More preferably, the structural orientation factor is 0.914-0.981. More preferably, the structural orientation factor is 0.917-0.952. More preferably, the structural orientation factor is 0.920-0.940. In a preferred embodiment, the structural orientation factor is 0.930.
[0021] According to the preparation method of the highly oriented structural thick film of the present invention, a straight line is used to form a dynamic shear flow field inside the two-dimensional nanosheet gel film layer and induce the orientation arrangement of the two-dimensional nanosheet layer, and a highly oriented thick film with a structural orientation factor of 0.91-0.99 can be prepared in the range of 80μm-400μm. The method is highly efficient and does not require complex equipment, is easy to scale up production continuously, and is suitable for the large-scale preparation of highly oriented structural macroscopic thick films of two-dimensional nanomaterials such as graphene oxide, graphene, boron nitride, and molybdenum disulfide, and has important application prospects in the fields of thermal conductivity, mechanics, and electromagnetic shielding. Compared with the prior art, the straight line penetration-induced bulk phase orientation strategy proposed in the present invention has two advantages: first, the shear flow field induced by the straight line penetration deeply disperses the liquid phase, which can realize the collective high orientation of countless two-dimensional sheets in the entire liquid phase space, and the prepared macroscopic structural thick film has a high degree of orientation; second, the method is compatible with traditional continuous film-making methods such as scraping, which solves the contradiction between efficiency and high orientation in the preparation of oriented structural thick films by traditional methods, and can realize the efficient continuous batch preparation of highly structural oriented two-dimensional nanosheet-based thick films. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process flow chart of the method for preparing a highly oriented structure thick film according to the present invention.
[0023] Figure 2 It is a schematic structural diagram of a device for preparing a highly oriented structural thick film according to a preferred embodiment of the present invention.
[0024] Figure 3 It is a schematic structural diagram of a device for preparing a highly oriented structural thick film according to another preferred embodiment of the present invention.
[0025] Figure 4 These are the actual pictures, wide-angle XRD patterns, and thermal conductivity test data of the highly oriented graphene thick film prepared according to Example 1 of the present invention.
[0026] Figure 5 These are the actual pictures, wide-angle XRD patterns, and thermal conductivity test data of the graphitized samples of the highly oriented graphene / polyimide composite thick film prepared according to Example 2 of the present invention.
[0027] Figure 6 These are the actual pictures, wide-angle XRD patterns, and thermal conductivity test data of the sample after graphitization of the highly oriented graphene oxide thick film prepared according to Example 3 of the present invention.
[0028] Figure 7 It is a physical picture and wide-angle XRD spectrum of the highly oriented boron nitride thick film prepared according to Example 4 of the present invention.
[0029] Figure 8 These are the actual pictures and wide-angle XRD patterns of the highly oriented boron nitride thick film prepared according to Example 5 of the present invention.
[0030] Fig. 9 It is a physical picture and wide-angle XRD spectrum of the highly oriented boron nitride thick film prepared according to Example 6 of the present invention.
[0031] Fig.10 It is a physical picture and wide-angle XRD spectrum of the highly oriented boron nitride thick film prepared according to Example 7 of the present invention.
[0032] Fig.11 These are the physical pictures, wide-angle XRD patterns, and thermal conductivity test data of the graphene thick film prepared according to Comparative Example 1 of the present invention.
[0033] Fig.12 These are the actual pictures, wide-angle XRD patterns, and thermal conductivity test data of the graphene oxide thick film prepared according to Comparative Example 2 of the present invention.
[0034] Fig.13 These are the actual pictures, wide-angle XRD patterns, and thermal conductivity test data of the graphene oxide thick film prepared according to Comparative Example 3 of the present invention.
[0035] Fig.14 It is a physical picture and wide-angle XRD spectrum of the boron nitride thick film prepared according to Comparative Example 4 of the present invention.
[0036] Fig.15 It is a physical picture and wide-angle XRD spectrum of the boron nitride thick film prepared according to Comparative Example 5 of the present invention.
[0037] Fig.16 It is a physical picture and wide-angle XRD spectrum of the boron nitride thick film prepared according to Comparative Example 6 of the present invention.
[0038] Fig.17 It is a physical picture and wide-angle XRD spectrum of the boron nitride thick film prepared according to Comparative Example 7 of the present invention.
[0039] Fig.18 It is a physical picture and wide-angle XRD spectrum of the boron nitride thick film prepared according to Comparative Example 8 of the present invention. DETAILED DESCRIPTION
[0040] The preferred embodiments of the present invention are given below in conjunction with the accompanying drawings and described in detail.
[0041] like Figure 1 As shown, the method for preparing a highly oriented structure thick film according to the present invention first comprises dispersing two-dimensional nanosheets in a solvent to form a two-dimensional nano dispersion. The two-dimensional nanosheets here can be graphene sheets, graphene oxide sheets, boron nitride nanosheets or molybdenum disulfide nanosheets, etc. The solvent here can be one of water or other organic solvents or a mixed system thereof. The two-dimensional nano dispersion here can contain inorganic materials or organic resins, etc. and the two-dimensional sheets to form a composite system.
[0042] like Figure 1 As shown, the method for preparing a highly oriented structure thick film according to the present invention then includes spreading / laying the two-dimensional nano-dispersion liquid on the surface of the substrate to form a gel film layer with randomly oriented sheets. The substrate here can be in the form of a film material, a tank or a mesh plate.
[0043] like Figure 1 As shown, the method for preparing a highly oriented structure thick film according to the present invention then includes a linear induced shear flow field for orientation treatment to form a gel film layer with highly oriented sheets. The orientation treatment here refers to inserting a plurality of straight lines parallel to the substrate plane into the interior of the gel film layer and causing relative movement with the gel film layer in a direction parallel to the substrate plane. In a preferred embodiment, as Figure 2 As shown, the substrate 1 is mounted on a fixed platform 11, the gel film layer 2 is laid flat on the substrate 1, and the plurality of straight lines 3 are mounted on a translation frame 31, so that the translation of the plurality of straight lines 3 relative to the gel film layer 2 is achieved by the linear motion of the translation frame 31. In another preferred embodiment, as Figure 3 As shown, the substrate 1' is mounted on a fixed platform 11', the gel film layer 2' is laid flat on the substrate 1', and the plurality of straight lines 3' are mounted on a rotating frame, so that the rotation of the rotating frame can realize the rotation of the plurality of straight lines 3' relative to the gel film layer 2'. The material of the straight lines can be metal, polymer, carbon fiber or a composite material thereof.
[0044] like Figure 1 As shown, the method for preparing a highly oriented structural thick film according to the present invention finally includes drying the oriented gel film layer to obtain a highly oriented two-dimensional nanosheet-based thick film.
[0045] Example 1
[0046] Prepare a graphene nanosheet / 1-methyl-2-pyrrolidone dispersion with a mass concentration (solid content) of 3wt% and a viscosity of 19930cps. Spread the dispersion on a polyethylene terephthalate (PET) film with a size of 10cm*10cm to form a gel film with a thickness of about 3mm with randomly oriented graphene sheets. Insert a wire frame wound with 8 parallel aluminum wires (diameter 0.1mm, wire spacing 0.3mm) into the above gel film layer, adjust the height of the parallel wire frame so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then fix the wire frame to a translation frame and move back and forth with the translation frame in a direction parallel to the substrate (device such as Figure 2 The gel film layer was dried in an oven at 80°C to obtain a dry film with an average thickness of 88.2 μm. The orientation degree of the film layer was measured by wide-angle X-ray diffraction (WAXS) to be 0.981 (as shown in FIG. Figure 4 The dry film was graphitized (2850°C, 4h heat preservation) and rolled to obtain a graphene thermal conductive film (thickness 81μm). The thermal conductivity of the graphene thermal conductive film was measured by laser scattering method (NETZSCH FL467) to be 1529.7W / (m·K).
[0047] Example 2
[0048] 0.5 wt% graphene nanosheets and 5 wt% polyvinylidene fluoride (5.63 × 10 5g / mol, Dongzhan Plastic Co., Ltd.) with a viscosity of 31050cps. The dispersion was spread in a concave trough of polyethylene terephthalate (PET) with a size of 5cm*10cm to form a gel film with a random orientation of graphene sheets with a thickness of about 7mm. A wire rack wound with 9 parallel carbon fiber wires (diameter 0.5mm, wire spacing 0.3mm) was inserted into the above-mentioned gel film layer, and the height of the parallel wire rack was adjusted so that the center height of all the wires inserted into the gel film layer as a whole was basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire rack was fixed to the translation frame and moved back and forth with the translation frame in a direction parallel to the substrate. The translation rate was 10mm / s, and the round-trip cycle was 5 times to obtain an oriented gel film layer. The above-mentioned gel film layer was dried in an oven at 100°C to obtain a dry film with a thickness of 387.7μm. The orientation degree of the film layer was measured by wide-angle X-ray diffraction (WAXS) to be 0.917 (such as Figure 5 The dry film was graphitized (2850°C, 4h heat preservation) and rolled under the same conditions as in Example 1 to obtain a graphene thermal conductive film (thickness 103 μm). The thermal conductivity of the graphene thermal conductive film was measured by laser scattering method (NETZSCH FL467) and was found to be 1655.4 W / (m·K).
[0049] Example 3
[0050] Prepare a graphene oxide aqueous dispersion with a mass concentration (solid content) of 6wt% and a viscosity of 43280cps. Spread the dispersion on a polyethylene terephthalate (PET) mesh plate (250 mesh) with a size of 10cm*10cm to form a gel film with randomly oriented graphene oxide sheets with a thickness of about 5mm. Insert a wire frame wound with 8 parallel polyester fiber lines (diameter 0.2mm, line spacing 0.5mm) into the above gel film layer, adjust the height of the parallel wire frame so that the center height of all the lines inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then fix the wire frame to a rotating frame and rotate with the rotating frame in a direction parallel to the substrate (device such as Figure 3 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 296.1 μm. The orientation degree of the film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.914 (as shown in FIG. Figure 6The dry film was graphitized (2850°C, 4h heat preservation) and rolled to obtain a graphene thermal conductive film (thickness 89 μm) under the same conditions as in Example 1. The thermal conductivity of the graphene thermal conductive film was measured by laser scattering method (NETZSCH FL467) and was found to be 1594.17 W / (m·K).
[0051] Example 4
[0052] A water / isopropanol dispersion having a mass concentration (solid content) of 1.5 wt% of boron nitride nanosheets is prepared, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 11140 cps. The dispersion is spread flat in a polyethylene terephthalate (PET) tank having a size of 10 cm*10 cm to form a gel film of randomly oriented boron nitride sheets having a thickness of about 15 mm. A wire frame wound with 25 parallel carbon fiber wires (diameter 0.5 mm, wire spacing 0.1 mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire frame is adjusted so that the center height of all the wires inserted into the gel film layer as a whole is substantially consistent with the middle height of the gel film layer (ensuring that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire frame is fixed to a translation frame and moves back and forth with the translation frame in a direction parallel to the substrate (device such as Figure 2 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 223.4 μm. The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.930 (as shown in FIG. Figure 7 shown).
[0053] Example 5
[0054] Prepare a water / isopropanol dispersion with a mass concentration (solid content) of 3 wt% of boron nitride nanosheets, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 19850 cps. Spread the dispersion on a polyethylene terephthalate (PET) film with a size of 10 cm*10 cm to form a gel film with a random orientation of boron nitride sheets with a thickness of about 5 mm. Insert a wire frame wound with 6 parallel carbon fiber wires (diameter 0.5 mm, wire spacing 0.3 mm) into the above-mentioned gel film layer, adjust the height of the parallel wire frame so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then fix the wire frame to a rotating frame and rotate with the rotating frame in a direction parallel to the substrate (device such as Figure 3 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 162.4 μm. The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.952 (as shown in FIG. Figure 8 shown).
[0055] Example 6
[0056] A boron nitride nanosheet mass concentration (solid content) of 7 wt% water / isopropanol dispersion is prepared, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 43480 cps. The dispersion is spread on a polyethylene terephthalate (PET) mesh plate (250 mesh) of size 10 cm*10 cm to form a gel film of randomly oriented boron nitride sheets with a thickness of about 5 mm. A wire frame wound with 7 parallel polyester fiber lines (diameter 0.2 mm, line spacing 0.5 mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire frame is adjusted so that the center height of all the lines inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire frame is fixed to a translation frame and moves back and forth with the translation frame in a direction parallel to the substrate (device such as Figure 2 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 355.2 μm. The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.940 (as shown in FIG. Fig. 9 shown).
[0057] Example 7
[0058] Prepare a water / isopropanol dispersion with a boron nitride mass concentration (solid content) of 1wt%, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 7273cps. Spread the dispersion in a polyethylene terephthalate (PET) tank with a size of 10cm*10cm to form a gel film of randomly oriented boron nitride sheets with a thickness of about 20mm. Insert a wire frame wound with 25 parallel carbon fiber wires (diameter 0.5mm, wire spacing 0.3mm) into the above-mentioned gel film layer, adjust the height of the parallel wire frame so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then fix the wire frame to a translation frame and move back and forth with the translation frame in a direction parallel to the substrate (device such as Figure 2 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 197.3 μm. The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.920 (as shown in FIG. Fig.10 shown).
[0059] Comparative Example 1
[0060] The corresponding process and parameters are the same as those in Example 1, but no orientation arrangement treatment is performed, that is, no straight line is used to move relative to each other in the gel film, and no shear flow field that induces sheet orientation is formed. The specific process is as follows: a graphene nanosheet / 1-methyl-2-pyrrolidone dispersion with a mass concentration (solid content) of 3wt% is prepared, and the viscosity of the dispersion is 19930cps. The dispersion is spread on a polyethylene terephthalate (PET) substrate with a size of 10cm*10cm to form a gel film with randomly oriented graphene sheets with a thickness of about 3mm. The above-mentioned gel film layer is dried in an oven at 80°C to obtain a dry film with an average thickness of 92.2μm. The film orientation degree is measured by wide-angle X-ray diffraction (WAXS) to be 0.809 (such as Fig.11 The dry film was graphitized (2850°C, 4h insulation) and rolled to obtain a graphene thermal conductive film (84 μm thick) under the same conditions as in Example 1. The thermal conductivity of the graphene thermal conductive film was measured by laser scattering method (NETZSCH FL467) to be 1048.81 W / (m·K).
[0061] Comparative Example 2
[0062] The corresponding process and parameters are the same as those in Example 3, but the two-dimensional nanosheet dispersion adopts a graphene oxide dispersion with a larger mass concentration (solid content), higher solid content and higher viscosity than that in Example 3. The specific process is as follows: a graphene oxide aqueous phase dispersion with a mass concentration (solid content) of 7.7wt% is prepared, and the viscosity of the dispersion is 50120cps. The dispersion is spread on a polyethylene terephthalate (PET) mesh plate (250 mesh) with a size of 10cm*10cm to form a gel film with a random orientation of graphene oxide sheets with a thickness of about 5mm. A wire frame wound with 8 parallel polyester fiber wires (diameter 0.2mm, wire spacing 0.5mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire frame is adjusted so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire frame is fixed to a rotating frame and rotates with the rotating frame in a direction parallel to the substrate (device such as Figure 3 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 377.2 μm. The orientation degree of the film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.802 (as shown in FIG. Fig.12 The dry film was graphitized (2850°C, 4h insulation) and rolled to obtain a graphene thermal conductive film (thickness 99 μm) under the same conditions as in Example 1. The thermal conductivity of the graphene thermal conductive film was measured by laser scattering method (NETZSCH FL467) to be 1276.79 W / (m·K).
[0063] Comparative Example 3
[0064] The corresponding process and parameters are the same as those in Example 3, but a larger rotation speed is used to generate a shear flow field and induce the orientation of two-dimensional sheets in the gel film layer. The specific process is as follows: prepare an aqueous dispersion of graphene oxide with a mass concentration (solid content) of 6wt%, and the viscosity of the dispersion is 43280cps. Use the dispersion to spread on a polyethylene terephthalate (PET) mesh plate (250 mesh) with a size of 10cm*10cm to form a gel film with randomly oriented graphene oxide sheets with a thickness of about 5mm. Insert a wire rack wound by 8 parallel polyester fiber lines (diameter 0.2mm, line spacing 0.5mm) into the above-mentioned gel film layer, adjust the height of the parallel wire rack so that the center height of all the lines inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then fix the wire rack to a rotating frame and rotate with the rotating frame in a direction parallel to the substrate (device such as Figure 3 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 314.6 μm. Visible holes and uneven surfaces (such as Fig.13 The film orientation was measured by wide angle X-ray diffraction (WAXS) to be 0.778. The dry film was graphitized (2850°C, 4h heat preservation) and rolled to obtain a graphene thermal conductive film (thickness 87μm) under the same conditions as in Example 1. The thermal conductivity of the graphene thermal conductive film was measured by laser scattering method (NETZSCH FL467) to be 1150.41W / (m·K).
[0065] Comparative Example 4
[0066] The corresponding process and parameters are the same as those in Example 5, but a smaller rotation speed is used to generate a shear flow field and induce the orientation of two-dimensional sheets in the gel film layer. The specific process is as follows: a water / isopropanol dispersion with a mass concentration (solid content) of 3wt% of boron nitride nanosheets is prepared, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 19850cps. The dispersion is spread on a polyethylene terephthalate (PET) film with a size of 10cm*10cm to form a gel film with a random orientation of boron nitride sheets with a thickness of about 5mm. A wire frame wound with 6 parallel carbon fiber wires (diameter 0.5mm, wire spacing 0.3mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire frame is adjusted so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire frame is fixed to a rotating frame and rotates with the rotating frame in a direction parallel to the substrate (device such as Figure 3 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 157.7 μm. The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.886 (as shown in FIG. Fig.14 shown).
[0067] Comparative Example 5
[0068] The corresponding process and parameters are the same as those in Example 7, but a smaller translation speed is used to generate a shear flow field and induce the orientation of two-dimensional sheets in the gel film layer. The specific process is as follows: a water / isopropanol dispersion with a boron nitride mass concentration (solid content) of 1wt% is prepared, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 7273cps. The dispersion is spread in a polyethylene terephthalate (PET) tank with a size of 10cm*10cm to form a gel film with a random orientation of boron nitride sheets with a thickness of about 20mm. A wire frame wound with 25 parallel carbon fiber wires (diameter 0.5mm, wire spacing 0.3mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire frame is adjusted so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire frame is fixed to the translation frame and moves back and forth with the translation frame in a direction parallel to the substrate (device such as Figure 2 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 193.7 μm. The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.802 (as shown in FIG. Fig.15 shown).
[0069] Comparative Example 6
[0070] The process and parameters are the same as those in Example 6, but a larger translation speed is used to generate a shear flow field and induce the orientation of two-dimensional sheets in the gel film layer. The specific process is as follows: a water / isopropanol dispersion with a mass concentration (solid content) of 7 wt% of boron nitride nanosheets is prepared, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 43480 cps. The dispersion is spread on a polyethylene terephthalate (PET) mesh plate (250 mesh) with a size of 10 cm*10 cm to form a gel film with a random orientation of boron nitride sheets with a thickness of about 5 mm. A wire frame wound with 7 parallel polyester fibers (diameter 0.2 mm, wire spacing 0.5 mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire frame is adjusted so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire frame is fixed to a translation frame and moves back and forth with the translation frame in a direction parallel to the substrate (device such as Figure 2 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 361.5 μm. Visible holes and uneven surfaces (such as Fig.16 The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) and was found to be 0.643.
[0071] Comparative Example 7
[0072] The corresponding process and parameters are the same as those in Example 5, but the wiring is less and the line spacing is larger. The specific process is as follows: a water / isopropanol dispersion with a mass concentration (solid content) of 3wt% of boron nitride nanosheets is prepared, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 19850cps. The dispersion is spread on a polyethylene terephthalate (PET) film with a size of 10cm*10cm to form a gel film with a random orientation of boron nitride sheets with a thickness of about 5mm. A wire rack wound with 4 parallel carbon fiber wires (diameter 0.5mm, wire spacing 0.9mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire rack is adjusted so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire rack is fixed to a rotating frame and rotates with the rotating frame in a direction parallel to the substrate (device such as Figure 3 The gel film layer was dried in an oven at 80°C to obtain a dry film with a thickness of 162.0 μm. The orientation degree of the dry film layer was measured by wide angle X-ray diffraction (WAXS) to be 0.813 (as shown in FIG. Fig.17 shown).
[0073] Comparative Example 8
[0074] The corresponding process and parameters are the same as those in Example 5, but there are more wires and the line spacing is smaller. The specific process is as follows: a water / isopropanol dispersion with a mass concentration (solid content) of 1.5wt% of boron nitride nanosheets is prepared, wherein the volume ratio of water to isopropanol is 1:1, and the viscosity of the dispersion is 11140cps. The dispersion is spread in a polyethylene terephthalate (PET) tank with a size of 10cm*10cm to form a gel film with a random orientation of boron nitride sheets with a thickness of about 15mm. A wire frame wound with 27 parallel carbon fiber wires (diameter 0.5mm, wire spacing 0.05mm) is inserted into the above-mentioned gel film layer, and the height of the parallel wire frame is adjusted so that the center height of all the wires inserted into the gel film layer as a whole is basically consistent with the middle height of the gel film layer (to ensure that the upper and lower surfaces of the gel film layer undergo the same flow field treatment process), and then the wire frame is fixed to the translation frame and moves back and forth with the translation frame in a direction parallel to the substrate (device such as Figure 2 The gel film layer was dried in an oven at 80°C to obtain a dry film with an average thickness of more than 200 μm. The thickness of different regions on the film surface varied greatly, with the thinnest being about 115 μm and the thickest being 245 μm. The orientation degree of the dry film layer was measured by wide-angle X-ray diffraction (WAXS) to be 0.520 (as shown in Figure 2). Fig.18 shown).
[0075] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.
Claims
1. A method for preparing a highly oriented structural thick film, characterized in that: The preparation method comprises the following steps: S1, dispersing the two-dimensional nanosheets in a solvent to obtain a two-dimensional nanodispersion liquid with a mass concentration of the two-dimensional nanosheets between 0.5 wt % and 7.0 wt %; S2, spreading the two-dimensional nano-dispersion liquid on the surface of the substrate to form a first gel film layer with randomly oriented flakes; S3, inserting a plurality of straight lines into the first gel film layer to induce a shear flow field for orientation treatment, so as to form a second gel film layer with highly oriented sheets, wherein the plane where the plurality of straight lines are located is parallel to the plane of the substrate and the spacing between adjacent straight lines is between 0.1 mm and 0.5 mm, and the straight lines and the first gel film layer move relative to each other in a direction parallel to the plane of the substrate, and the relative movement is a translational motion at a speed between 3 mm / s and 16 mm / s or a rotational motion at a speed between 600 rpm and 1100 rpm; S4, drying the second gel film layer to obtain a highly structurally oriented two-dimensional nanosheet-based thick film.
2. The preparation method according to claim 1, characterized in that: The two-dimensional nanosheet is a graphene sheet, a graphene oxide sheet, a boron nitride nanosheet or a molybdenum disulfide nanosheet.
3. The preparation method according to claim 1, characterized in that: The mass concentration of the two-dimensional nanosheets in the two-dimensional nanodispersion liquid is between 1wt% and 6wt%.
4. The preparation method according to claim 1, characterized in that: The viscosity of the two-dimensional nano-dispersion liquid is 7000cps-45000cps.
5. The preparation method according to claim 1, characterized in that: The thickness of the first gel film layer is 3 mm-20 mm.
6. The preparation method according to claim 1, characterized in that: The diameter of the straight line is 0.1mm-0.5mm.
7. The preparation method according to claim 1, characterized in that: The spacing between adjacent straight lines is 0.2mm-0.3mm.
8. The preparation method according to claim 1, characterized in that: The translation speed is between 4mm / s-15mm / s, and the rotation speed is between 700rpm-1000rpm.
9. The preparation method according to claim 1, characterized in that: The thickness of the two-dimensional nanosheet-based thick film is 80 μm-400 μm.
10. The preparation method according to claim 1, characterized in that: The structural orientation factor of the two-dimensional nanosheet-based thick film is 0.91-0.99.